2014
DOI: 10.1212/wnl.0000000000000669
|View full text |Cite
|
Sign up to set email alerts
|

The burden of Duchenne muscular dystrophy

Abstract: Objective:The objective of this study was to estimate the total cost of illness and economic burden of Duchenne muscular dystrophy (DMD).Methods:Patients with DMD from Germany, Italy, United Kingdom, and United States were identified through Translational Research in Europe–Assessment & Treatment of Neuromuscular Diseases registries and invited to complete a questionnaire online together with a caregiver. Data on health care use, quality of life, work status, informal care, and household expenses were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
173
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(185 citation statements)
references
References 14 publications
11
173
1
Order By: Relevance
“…Indeed patients may not remember their use of healthcare resources accurately and may simply guess, leading to an under-or overestimation of costs [14]. It should also be noted that some of the cost estimations may have been more sensitive than others to recall bias as patients are more likely to remember large or recurrent expenses than small or rare ones [57]. The use of an online questionnaire may also skew the patient or caregiver population towards younger, better educated, healthier and wealthier individuals with easy access to the Internet, and we cannot therefore rule out a degree of selection bias in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed patients may not remember their use of healthcare resources accurately and may simply guess, leading to an under-or overestimation of costs [14]. It should also be noted that some of the cost estimations may have been more sensitive than others to recall bias as patients are more likely to remember large or recurrent expenses than small or rare ones [57]. The use of an online questionnaire may also skew the patient or caregiver population towards younger, better educated, healthier and wealthier individuals with easy access to the Internet, and we cannot therefore rule out a degree of selection bias in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Duchenne muscular dystrophy (DMD) and the less severe form Becker muscular dystrophy (BMD) comprise the most common forms of muscular dystrophies with approximate 1:5000 boys [1]. They are caused by mutations in the largest human gene encoding dystrophin protein spanning 79 exons on chromosome Xp21 which makes full gene assessment difficult and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…From around 8 years of age, the median age of boys entering our study, families will typically make investments in and reconstructions of the home, for instance making adaptations for wheelchair accessibility. 24 Adaptations may also be required to educational facilities. A systematic review of the cost of illness 4 noted only three studies that reported cost-impact data, all of which were > 20 years old.…”
Section: Significance In Terms Of Ill Healthmentioning
confidence: 99%
“…A systematic review of the cost of illness 4 noted only three studies that reported cost-impact data, all of which were > 20 years old. [25][26][27] However, a questionnaire study 24 involving people with DMD in Germany, Italy, the UK and the USA provided per-patient annual costs of DMD in 2012 in international dollars. The questionnaire elicited information about hospital admissions, visits to health-care professionals, tests, assessments, medications, non-medical community services, aids, devices, alterations to the home and informal care.…”
Section: Significance In Terms Of Ill Healthmentioning
confidence: 99%